INSIDE THE CHILD CARE CENTER: HOW TO ENSURE QUALITY CHILD CARE PRACTICES - Hanafi, Zahyah; Noor Ismail, Siti (International Journal of Education, 2014)
Ensuring staff display best practices when handling children at childcare center is a task that requires the management to instil knowledge of child development and develop the skills for maintaining childcare. This paper unfolds the initiative of a childcare manager who believes in the necessity of conducting research about staff skills and level of knowledge to ensure the quality of childcare service. Therefore, a case study was conducted to identify the key areas of a quality childcare centre: staff relationships with children and peers, partnerships with families, programming and evaluation, children’s experiences and learning, protective care and safety, health, nutrition and well-being, and management to support quality. The questionnaire was adapted from the Quality Improvement Accreditation System (QIAS) model and administered to all staffs at the center. This research discovers three areas in which each of them (1) reflect staffs' ability to implement new knowledge; (2) need further training and guidance; and (3) need urgent consistent training and monitoring. Furthermore, this study also presents discussion between the researcher and the manager to enhance staff development.